Tribological Behavioural Of Bio-Oil Extracted From Peel Waste Of Musa Aluminata Balbisiana - Omar, Ghazali; A Hamid, Husna; Masripan, Nor Azmmi; Hasan, Rafidah (Japanese Society of Tribologists, 2020)
The aim of this study is to investigate the effects of applied loads and temperatures on the tribological properties of MBS oil, which is a bio-oil extracted from banana peel waste of Musa Aluminata Balbisiana, MBS. Tribological evaluation of MBS oil was conducted using pin on disc tribometer as per G 99 ASTM standard. In this method, hemisphere pin was loaded against the rotating disc containing the MBS oil. The test was implemented by dropping 2 ml of MBS oil as a lubricating oil on sliding surface at varying loads from 20 to 100 N at 27°C, 40°C and 100°C. The results showed that, at 80 N, the coefficient of friction (COF), volume wear loss (Vloss), wear scar diameter (WSD), and wear rate (Ws) values were lower at all the tested temperatures. Microscopic analysis revealed that, the above results is due to the formation of tribo-chemical film which existed as protective layer on sliding surface thus preventing metal to metal contacted each other, hence contributed to the favor of frictional reduction.